Approach to the new dynamics of the Traditional Banking Model in Colombia versus the Fintech Model. 2021 - Vega Zuluaga, Juan David
The purpose of this research is to make an approach to the new dynamics of the Traditional Banking Model in Colombia versus the Fintech Model, reviewing updated primary and secondary sources on the subject, attending to the opinion of experts on the subject available on the web, finally building a possible direction or dynamics of the sector in Colombia. The research is descriptive in nature and in order to achieve the proposed objectives, two information gathering instruments were used, such as the analysis of the opinion of experts in the fintech area, and the direct observation of the indicators of the control and supervisory entities, as well as of the companies that make up the local ecosystem. It is determined that the emergence of fintechs in the financial sector, originate a collaborative, complementary or associative relationship, according to the particularities of each Startup, and allow a different way of presenting and offering a new portfolio of services of traditional financial institutions with decades of presence in the market. Likewise, the massification of the Internet, the growing interaction on the network, the reduction of costs and operating expenses in their processes, becomes the greatest of its advantages, being catapulted some fintechs in the financial sector by the pandemic. The interest of traditional banking vis-à-vis fintechs is mutual, since the union of the two becomes a source of competitive advantage in the financial market when an effective integration is achieved between the needs of one (traditional banking) and the technological developments and connectivity of the other (fintechs). Regarding the benefits and risks of the arrival of fintechs in Colombia, it is considered that some of the greatest benefits are related to the different techniques of identity verification and thus avoiding the displacement of users to different financial entities and branches. Another benefit that has helped the consolidation of fintechs is related to the activation time of a financial product or service, which is shorter in fintechs and with less paperwork.